Neonatal Nutrition for Inflammatory Disorders and Necrotizing Enterocolitis - Good, Misty (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Nutrients Special Issue focuses on neonatal nutritional advances for inflammatory disorders affecting infants such as necrotizing enterocolitis (NEC). Nutrition can significantly impact the development of certain diseases that afflict infants. This Special Issue aims to bring together the latest research on the role of nutrition in preventing or impacting neonatal disorders. Specifically, this Special Issue focuses on the role of breast milk or donor breast milk and the various components in milk that have been demonstrated to protect against NEC and other inflammatory diseases. This issue provides a comprehensive composite of the advances in nutritional strategies that can modulate or prevent neonatal intestinal disorders.